Impact of sex, socio‐economic status, and remoteness on therapy and survival in heart failure. (16th October 2019) - Gutman, Sarah J.; Costello, Ben T.; Papapostolou, Stavroula; Iles, Leah; Ja, Johnson; Hare, James L.; Ellims, Andris; Marwick, Thomas H.; Taylor, Andrew J.
Abstract: Aims: This study aims to determine if traditional markers of disadvantage [female sex, low socio‐economic status (SES), and remoteness] are associated with lower prescription of evidence‐based therapy and higher mortality among patients with moderate–severe heart failure with reduced ejection fraction. Methods and results: We recruited 452 consecutive class II–III heart failure with reduced ejection fraction patients. Baseline clinical data were recorded prospectively. The primary outcome was the association of female sex on overall survival. Secondary outcomes included association between evidence‐based therapy delivery and sex and association of SES and remoteness on heart failure therapy and survival. The Australian Bureau of Statistics generated all indices. Median follow‐up was 37.9 months. One hundred and nine patients (24.3%) were women. There was no difference in overall survival based on sex (hazard ratio = 1.19, 95% confidence interval: 0.74–1.92, 0.48). There was no difference in prescription of beta‐blockers [ χ 2 (1) = 0.91, 0.66], angiotensin‐converting enzyme inhibitors [ χ 2 (1) = 0.001, 0.97], nor aldosterone antagonists [ χ 2 (1) = 2.71, 0.10]. There was no difference in rates of primary prevention implantable cardioverter‐defibrillator implantation in men compared with women [ χ 2 (1) = 0.35, 0.56]. Neither higher SES nor inner city residence conferred an overall survival benefit. Conclusions: In this Australian cohort of heart failure patients, delivery of care and likelihood of death are comparable between the sexes, SES groups, and rural vs. city residents.